Measuring the Angle of the Subpubic Arch Using Three-Dimensional Transperineal Ultrasound Scan: Intraoperator Repeatability and Interoperator Reproducibility - Choi, Sarah; Chan, Symphorosa Shing Chee; Sahota, Daljit Singh; Leung, Tak Yeung (American Journal of Perinatology, 2013)
Objective A method of measuring the subpubic arch angle using three-dimensional transperineal ultrasound scan (3DTUS) was developed, and the intraoperator repeatability and interoperator reproducibility were investigated.Study Design Using 3DTUS, volume data sets were obtained from the nine nulliparous pregnant women by three operators (A, B, and C) in each of the three study sessions. With volume reconstruction, a plane along the inferior edges of bilateral inferior pubic rami was obtained on the axial section. The angle made between the innermost points of both inferior pubic rami at the level of urethra and the inferoposterior point of symphysis pubis was measured as the subpubic arch angle. The intraoperator repeatability of the experienced operator (A) and the interoperator reproducibility between A, B, and C were assessed by the repeatability coefficient and the interoperator intraclass correlation (ICC), respectively.Results A total of 27 women were examined. The intraoperator repeatability was 4.73 degrees. The overall interoperator ICC was 0.860, and increased from 0.794 in the first session to 0.945 in the third session.Conclusion With 3DTUS, it is feasible to measure subpubic arch angle with satisfactory intraoperator repeatability and interoperator reproducibility. This easy-to-learn technique extends the possibilities of future pelvimetry research using 3DTUS.
Keywords: subpubic arch angle; transperineal ultrasound; repeatability; reproducibility; intraoperator; interoperator